2020
DOI: 10.7150/ijms.43491
|View full text |Cite
|
Sign up to set email alerts
|

HBx mediated Increase of SIRT1 Contributes to HBV-related Hepatocellular Carcinoma Tumorigenesis

Abstract: Objective: Hepatocellular carcinoma (HCC) is one of the main causes of cancer-related deaths worldwide, and chronic hepatitis B virus (HBV) infection is strongly associated with HCC development, but the pathogenesis of HBV-related HCC remains obscure. Sirtuin 1 (SIRT1) has been implicated to enhance the replication of HBV and to promote the tumorigenesis of HCC. In this study, we aim to investigate the functional role of SIRT1 on HBV viral protein and HBV-induced HCC. Methods: Tumorous liver tissues from patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…Sirtuin 6 promotes the transcription and replication of HBV by upregulating the expression of peroxisome proliferator-activated receptor α (34). In addition, sirtuin 1 has been shown to be essential for HBV-associated liver cancer tumorigenesis (35)(36)(37). Therefore, the reduction of NAD synthesis by NAMPT inhibition may be an effective and promising method for the treatment of patients with HBV-associated liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Sirtuin 6 promotes the transcription and replication of HBV by upregulating the expression of peroxisome proliferator-activated receptor α (34). In addition, sirtuin 1 has been shown to be essential for HBV-associated liver cancer tumorigenesis (35)(36)(37). Therefore, the reduction of NAD synthesis by NAMPT inhibition may be an effective and promising method for the treatment of patients with HBV-associated liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Wang et al showed that, compared with those in the hepatoma cell line HepG2, the levels of SIRT1 mRNA and its protein were increased in HepG2.2.15 (HepG2 harboring HBV genome). Additionally, the HBV-mediated alteration in SIRT1 expression was further confirmed in HepAD38 cells, in which HBVs were continuously produced in the presence of tetracycline ( 14 ). Among the HBV-encoded proteins, only HBx has been found to increase SIRT1 expression at the mRNA and protein levels ( 14 ).…”
Section: Effect Of Hbv On Sirtsmentioning
confidence: 92%
“…Additionally, the HBV-mediated alteration in SIRT1 expression was further confirmed in HepAD38 cells, in which HBVs were continuously produced in the presence of tetracycline ( 14 ). Among the HBV-encoded proteins, only HBx has been found to increase SIRT1 expression at the mRNA and protein levels ( 14 ). The expression of HBx could also be upregulated by SIRT1 in the HBV-expressing hepatocytes.…”
Section: Effect Of Hbv On Sirtsmentioning
confidence: 92%
See 2 more Smart Citations